2016
DOI: 10.4028/www.scientific.net/msf.866.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fly Ash and Basalt Fibers on Strength and Chloride Penetration Resistance of Self-Consolidating Concrete

Abstract: Fly ash is a sustainable partial replacement of Portland cement that offers significant advantages in terms of fresh and hardened properties of concrete. This paper presents the findings of a study that aims at assessing the durability and strength properties of sustainable self-consolidating concrete (SCC) mixes in which Portland cement was partially replaced with 10%, 20%, 30%, and 40% fly ash. The study confirms that replacing Portland cement with fly ash at all of the percentages studied improves resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Moreover, an increase in the tricalcium aluminate content of concrete increases the chloride binding capacity of concrete [10]. e inverse relationship between FA and RCP has also been observed past research [67]. A decrease in the electrical conductivity of concrete has also been reported with the addition of slag in the binder of HSC [43].…”
Section: Rapid Chloride Permeability (Rcp)supporting
confidence: 56%
“…Moreover, an increase in the tricalcium aluminate content of concrete increases the chloride binding capacity of concrete [10]. e inverse relationship between FA and RCP has also been observed past research [67]. A decrease in the electrical conductivity of concrete has also been reported with the addition of slag in the binder of HSC [43].…”
Section: Rapid Chloride Permeability (Rcp)supporting
confidence: 56%
“…ANN models were developed to predict chloride penetration levels in concrete where the cement was partially replaced with various amounts of minerals including fly ash, silica fume, and slag as demonstrated in this paper. Experimental data on the influence of fly ash and basalt fibers on strength and chloride penetration resistance of SCC was presented by Mohamed and Al-Hawat [1]. Mechanical properties of SCC examined in this study, such as splitting tensile strength, were reported by Mohamed and Najm [2] and Mohamed et al [3].…”
Section: Introductionmentioning
confidence: 60%
“…In general, the effect of basalt fibers on fresh and mechanical properties of concrete depends on the mechanical and geometric properties of the basalt fibers themselves, in addition to concrete mix constituents and additives. Studies have shown that in the presence of fly ash, a dosage of 1% basalt fibers by volume produced optimum results for concrete strength and resistance to chloride penetration resistance, compared to higher or lower dosages [ 38 ].…”
Section: Flexural Response and Contribution To Compression Forcesmentioning
confidence: 99%